A method for preparing spherical silicon powder for LED display device packaging material
The method addresses agglomeration and compatibility issues in spherical silicon micropowder by using PEG1500 and surface modification with 3,5-di-tert-butyl-4-hydroxybenzylamine, enhancing dispersion and mechanical properties in epoxy molding compounds for LED display devices.
Patent Information
- Application Number
- CN202410656137.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-24
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-05-24
AI Technical Summary
Existing methods for preparing spherical silicon micropowder for LED display device packaging materials face challenges such as high-temperature agglomeration, poor dispersion in organic matrices, and compatibility issues with epoxy molding compounds, leading to reduced mechanical properties and antioxidant performance.
A method involving the use of PEG1500 and calcination in nitrogen and air atmospheres, combined with surface modification using 3,5-di-tert-butyl-4-hydroxybenzylamine antioxidant, to prevent agglomeration and enhance dispersion and compatibility of spherical silicon micropowder in epoxy molding compounds.
The method results in improved mechanical properties and antioxidant performance of the epoxy molding compound, with enhanced dispersion and compatibility of spherical silicon micropowder, reducing agglomeration and maintaining mechanical integrity under high temperatures.
Smart Images

Figure BDA0004857889890000101 
Figure BDA0004857889890000111 
Figure BDA0004857889890000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of spherical silicon micropowder preparation, and in particular relates to a method for preparing spherical silicon micropowder for LED display device packaging material. Background Art
[0002] Light-emitting diodes (LEDs) are semiconductor light-emitting devices that can convert electrical energy into light energy. They are widely used in various display technologies, such as general lighting, backlight sources, indicator signals, and optical communication light sources, due to their high luminous efficiency, environmental protection, resistance to damage, and long life. However, with the continuous improvement of the performance and reliability of LED chips, packaging materials have become one of the key technologies restricting their rapid development. In order to prepare long-life, high-efficiency LED devices, packaging materials are required to have high brightness and high reliability, including high refractive index, high light transmittance, resistance to heat oxygen aging and ultraviolet aging, low thermal expansion coefficient, low stress, and low hygroscopicity.
[0003] Epoxy molding compound is an essential material for LED display device packaging, and spherical silicon powder has excellent properties such as high heat resistance, high moisture resistance, high filling rate, low expansion, low stress, low impurities, and low friction coefficient, making it an indispensable functional filling material in ultra-large-scale and ultra-large-scale integrated circuit packaging materials. The addition of spherical silicon powder can effectively reduce the water absorption and thermal expansion coefficient of the packaging material, thereby avoiding the "popcorn" phenomenon caused by moisture absorption during the reflow soldering process, and reducing the wet stress caused by water absorption and expansion of the system and the thermal stress caused by mismatch of thermal expansion coefficients on the reliability of LEDs.
[0004] At present, the preparation methods of spherical silicon micropowder mainly include physical method and chemical method. The physical method mainly includes flame spheroidization method, high temperature melt spraying method, self-propagating low temperature combustion method and plasma method. The raw material quartz required for the physical method to prepare spherical silicon micropowder has a wide source and low cost, but it has high requirements on the quality of quartz raw materials and production equipment. The chemical method mainly includes gas phase method, hydrothermal synthesis method, self-propagating low temperature combustion method, sol-gel method, precipitation method and microemulsion method. Among them, the precipitation method has the characteristics of simple process, wide source of raw materials, low equipment requirements, and industrial production. However, the preparation process requires high temperature calcination, and the high temperature calcination process is very easy to cause hard agglomeration of spherical silicon micropowder, resulting in relatively low product quality, which limits its application.
[0005] In addition, as an inorganic material, spherical silicon powder has different interface properties from the organic matrix of epoxy molding compound, and has poor compatibility with each other, making it difficult to disperse evenly in the organic matrix. At the same time, due to the large specific surface area and high surface free energy of spherical silicon powder, it is very easy to agglomerate, settle, and phase separate after being added to epoxy molding compound, so that the characteristics of spherical silicon powder in epoxy molding compound are difficult to be effectively exerted. Too much or direct filling of spherical silicon powder into the organic matrix can easily lead to problems such as decreased mechanical properties of composite materials and even embrittlement. Moreover, epoxy molding compound generally has high-temperature aging behavior. Under high temperature conditions, the light components inside the material are easy to volatilize. With the increase of aging time and the rise of temperature, the functional groups inside the epoxy molding compound will change, and the chemical bonds within or between molecules will break, resulting in changes in mechanical properties. Summary of the invention
[0006] In order to solve the deficiencies mentioned in the above background technology, the purpose of the present invention is to provide a method for preparing spherical silicon micropowder for LED display device packaging materials, by adding PEG1500 and calcining in nitrogen and air atmosphere to prevent high-temperature hard agglomeration of particles, and modifying the surface of the primary product with 3,5-di-tert-butyl-4-hydroxybenzylamine antioxidant, it is beneficial to the dispersion of spherical silicon micropowder in the organic matrix of epoxy molding compound, while giving the epoxy molding compound more excellent mechanical properties and antioxidant properties.
[0007] The purpose of the present invention can be achieved by the following technical solutions:
[0008] A method for preparing spherical silicon powder for LED display device packaging material comprises the following steps:
[0009] S1, dissolving fatty alcohol polyoxyethylene ether and anhydrous ethanol in deionized water, stirring and mixing at room temperature, adding sodium silicate solution and continuing to stir at a constant speed, then adding ethyl acetate, filtering and washing the product to prepare a filter cake;
[0010] S2, adding PEG1500 and deionized water to the filter cake, stirring and mixing at 45-60° C. and drying to prepare powder A;
[0011] S3, placing powder A in a tube furnace and calcining in a nitrogen atmosphere to prepare powder B;
[0012] S4, placing powder B in a muffle furnace and calcining in an air atmosphere to obtain powder C;
[0013] S5, placing powder C in a muffle furnace, and continuing to calcine in an air atmosphere to obtain a primary product;
[0014] S6, taking the initial product and adding deionized water, stirring and mixing at room temperature and ultrasonically dispersing, adding sodium chloroacetate, dropping sodium hydroxide solution to adjust the pH to 11-13, heating in an oil bath at 100-120° C. for 3-5 hours, cooling to room temperature and repeatedly washing with deionized water until the pH is neutral, then centrifuging and drying to prepare a carboxylated initial product;
[0015] S7, taking the initial carboxylation product, adding thionyl chloride, adding N,N-dimethylformamide after ultrasonic oscillation, placing in an oil bath at 80-95° C., stirring and reacting for 18-26 hours, filtering, washing, and drying to obtain an initial acyl chloride product;
[0016] S8. Take the initial product of acyl chloride and add tetrahydrofuran solvent. After ultrasonic dispersion, add 3,5-di-tert-butyl-4-hydroxybenzylamine and triethylamine, stir and mix evenly, place in a 15-40°C water bath and stir to react for 6-18 hours. After the reaction is completed, centrifuge to remove the supernatant, and vacuum dry to prepare spherical silicon micropowder.
[0017] Preferably, the concentration of the sodium silicate solution in step S1 is 0.4-0.6 mol / L, the stirring speed is 450-600 r / min, and the stirring time is 4-7 h.
[0018] Preferably, in step S1, the mass ratio of fatty alcohol polyoxyethylene ether, anhydrous ethanol, deionized water, sodium silicate solution and ethyl acetate is 4-8:10-15:90-150:80-120:14-20.
[0019] Preferably, in step S2, the mass ratio of the filter cake, PEG1500 and deionized water is 10:0.25-0.75:50.
[0020] Preferably, in step S3, the calcination temperature is 280-350° C., and the calcination time is 1-2 hours.
[0021] Preferably, in step S4, the calcination temperature is 300-350° C., and the calcination time is 1-2 hours.
[0022] Preferably, in step S5, the calcination temperature is 600-700° C., and the calcination time is 2-3 hours.
[0023] Preferably, in step S6, the mass ratio of the initial product to sodium chloroacetate is 1:1.2-2.
[0024] Preferably, in step S7, the addition ratio of the carboxylation initial product and thionyl chloride is 1 g: 60-100 mL.
[0025] Preferably, in step S8, the mass ratio of the initial product of acyl chloride, 3,5-di-tert-butyl-4-hydroxybenzylamine and triethylamine is 1:0.5-2:0.02-0.1.
[0026] Beneficial effects of the present invention:
[0027] The present invention adds raw material sodium silicate, precipitant ethyl acetate, dispersant anhydrous ethanol, surfactant fatty alcohol polyoxyethylene ether, and steric hindrance barrier PEG1500, adopts coprecipitation method and performs calcination in nitrogen and air atmosphere to prepare the primary product. The present invention first adds ethyl acetate to the sodium silicate solution, the pH of the system gradually decreases with the slow hydrolysis of ethyl acetate, the silicate ions undergo polymerization reaction when the alkalinity decreases, the oligomeric silicate ions polymerize to form high-polymer silicate ions, the high-polymer silicate ions in the form of colloidal particles will further polymerize, so that the colloidal particles become larger in size, and thus precipitate from the system in the form of precipitation; ethyl acetate, as a potential acidifier, can uniformly reduce the alkalinity of the system and effectively control the uniform precipitation of the precipitate; the added anhydrous ethanol can generate oxygen bonds with the Si-O structure, preventing the formation of Si-O-Si structure between particles, thereby playing a role in preventing agglomeration, and at the same time, the anhydrous ethanol inhibits the hydrolysis of ethyl acetate to a certain extent, thereby further achieving the goal of slowing down the alkalinity of the system. The purpose of slow reduction; fatty alcohol polyoxyethylene ether is a non-ionic surfactant with high water solubility and stability. It can reduce the solid-liquid surface tension and van der Waals force between particles in the liquid medium, making the particles dispersed and stable, and at the same time can form a steric stabilizing effect. In addition, it is easy to remove during the washing process and easy to volatilize during the drying and calcination processes, and avoids the introduction of ionic surfactants and thus avoids the introduction of impurity ions; PEG1500 is a chain polymer that will undergo carbonization in a high-temperature nitrogen atmosphere. The formed carbide can well wrap the primary product, produce a steric hindrance, and avoid direct contact between particles. Afterwards, the carbide is converted into carbon dioxide under high temperature in an air atmosphere, and the carbide disappears leaving holes, thereby blocking the high-temperature hard agglomeration of the particles.
[0028] The invention prepares a carboxylated primary product by heating a primary product and sodium chloroacetate under alkaline conditions, reacts the obtained carboxylated primary product with thionyl chloride, introduces an acyl chloride group on the surface of the primary product, and then reacts with an amino group on the surface of an antioxidant 3,5-di-tert-butyl-4-hydroxybenzylamine to graft the antioxidant onto the surface of the primary product, thereby preparing spherical silicon micropowder. Under the action of chemical bonds, the hindered phenol antioxidant and the primary product are more closely combined, the migration phenomenon of the hindered phenol antioxidant in an organic matrix of an epoxy molding compound is restricted, and the dispersion of the spherical silicon micropowder is facilitated, the compatibility of the spherical silicon micropowder and the organic matrix is improved, the interface bonding ability of the two is enhanced, the characteristics of the spherical silicon micropowder in the epoxy molding compound are effectively exerted, and the epoxy molding compound is endowed with good mechanical properties and antioxidant effects. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Embodiment 1 A method for preparing spherical silicon powder for LED display device packaging material comprises the following steps:
[0031] S1, take 4.2g fatty alcohol polyoxyethylene ether and 10g anhydrous ethanol and dissolve them in 100g deionized water, stir and mix at 450r / min at room temperature, add 85g 0.4mol / L sodium silicate solution and continue stirring at a constant speed, then add 16g ethyl acetate, filter and wash the product to prepare a filter cake;
[0032] S2. Add 0.25 g of PEG1500 and 50 g of deionized water to 10 g of the filter cake, stir and mix at 50° C., and then dry to prepare powder A;
[0033] S3, placing powder A in a tube furnace, and calcining at 280° C. for 1 h in a nitrogen atmosphere to prepare powder B;
[0034] S4, placing powder B in a muffle furnace, and calcining at 300° C. for 1 h in an air atmosphere to obtain powder C;
[0035] S5, placing powder C in a muffle furnace, and continuing to calcine at 600° C. for 2 h in an air atmosphere to obtain a primary product;
[0036] S6, take 10g of the initial product, add 100mL of deionized water, stir and mix at room temperature and ultrasonically disperse, add 12.3g of sodium chloroacetate, add a 0.1mol / L sodium hydroxide solution dropwise to adjust the pH to 11, heat in an oil bath at 100°C for 3h, cool to room temperature and repeatedly wash with deionized water until the pH is neutral, then centrifuge and dry to prepare a carboxylated initial product;
[0037] S7, take 1g of the initial carboxylation product, add 60mL of dichlorothionyl, add 2mL of N,N-dimethylformamide after ultrasonic oscillation, place in an 80°C oil bath, stir and react for 18h, filter, wash and dry to obtain the initial acyl chloride product;
[0038] S8. Take 1 g of the initial product of acyl chloride and add 15 mL of tetrahydrofuran solvent. After ultrasonic dispersion, add 0.5 g of 3,5-di-tert-butyl-4-hydroxybenzylamine and 0.02 g of triethylamine. Stir and mix evenly. Place in a 15°C water bath and stir to react for 12 hours. After the reaction is completed, centrifuge to remove the supernatant and vacuum dry to prepare spherical silicon powder.
[0039] Embodiment 2 A method for preparing spherical silicon powder for LED display device packaging material comprises the following steps:
[0040] S1, take 6.3g fatty alcohol polyoxyethylene ether and 12g anhydrous ethanol and dissolve them in 120g deionized water, stir and mix at 550r / min at room temperature, add 100g 0.5mol / L sodium silicate solution and continue stirring at a constant speed, then add 18g ethyl acetate, filter and wash the product to prepare a filter cake;
[0041] S2. Add 0.5 g PEG1500 and 50 g deionized water to 10 g of the filter cake, stir and mix at 45° C., and then dry to prepare powder A;
[0042] S3, placing powder A in a tube furnace, and calcining at 300° C. for 2 h in a nitrogen atmosphere to obtain powder B;
[0043] S4, placing powder B in a muffle furnace, and calcining at 320° C. for 2 h in an air atmosphere to obtain powder C;
[0044] S5, placing powder C in a muffle furnace, and continuing to calcine at 650° C. for 3 h in an air atmosphere to obtain a primary product;
[0045] S6, take 10g of the initial product, add 100mL of deionized water, stir and mix at room temperature and ultrasonically disperse, add 14.8g of sodium chloroacetate, add a 0.1mol / L sodium hydroxide solution dropwise to adjust the pH to 12, heat in an oil bath at 120°C for 4h, cool to room temperature and repeatedly wash with deionized water until the pH is neutral, then centrifuge and dry to prepare a carboxylated initial product;
[0046] S7, take 1g of the initial carboxylation product, add 80mL of dichlorothionyl, add 3mL of N,N-dimethylformamide after ultrasonic oscillation, place in an 85°C oil bath and stir to react for 24h, filter, wash and dry to obtain the initial acyl chloride product;
[0047] S8. Take 1 g of the initial product of acyl chloride and add it into 30 mL of tetrahydrofuran solvent. After ultrasonic dispersion, add 1.4 g of 3,5-di-tert-butyl-4-hydroxybenzylamine and 0.08 g of triethylamine. Stir and mix evenly. Place in a 30°C water bath and stir to react for 12 hours. After the reaction is completed, centrifuge to remove the supernatant and vacuum dry to prepare spherical silicon powder.
[0048] Embodiment 3 A method for preparing spherical silicon powder for LED display device packaging material comprises the following steps:
[0049] S1, take 8g fatty alcohol polyoxyethylene ether and 15g anhydrous ethanol and dissolve them in 150g deionized water, stir and mix at 600r / min at room temperature, add 120g 0.6mol / L sodium silicate solution and continue stirring at a constant speed, then add 20g ethyl acetate, filter and wash the product to prepare a filter cake;
[0050] S2. Add 0.75 g of PEG1500 and 50 g of deionized water to 10 g of the filter cake, stir and mix at 60° C., and then dry to prepare powder A;
[0051] S3, placing powder A in a tube furnace, and calcining at 350° C. for 1 h in a nitrogen atmosphere to obtain powder B;
[0052] S4, placing powder B in a muffle furnace, and calcining at 350° C. for 1 h in an air atmosphere to obtain powder C;
[0053] S5, placing powder C in a muffle furnace, and continuing to calcine at 700° C. for 2 h in an air atmosphere to obtain a primary product;
[0054] S6, take 10g of the initial product, add 100mL of deionized water, stir and mix at room temperature and ultrasonically disperse, add 16.6g of sodium chloroacetate, add a 0.1mol / L sodium hydroxide solution dropwise to adjust the pH to 13, heat in an oil bath at 120°C for 5h, cool to room temperature and repeatedly wash with deionized water until the pH is neutral, then centrifuge and dry to prepare a carboxylated initial product;
[0055] S7, take 1g of the initial carboxylation product, add 100mL of dichlorothionyl, add 3mL of N,N-dimethylformamide after ultrasonic oscillation, place in a 95°C oil bath and stir to react for 26h, filter, wash and dry to obtain the initial acyl chloride product;
[0056] S8. Take 1 g of the initial product of acyl chloride and add it to 40 mL of tetrahydrofuran solvent. After ultrasonic dispersion, add 2 g of 3,5-di-tert-butyl-4-hydroxybenzylamine and 0.1 g of triethylamine. Stir and mix evenly. Place in a 40°C water bath and stir to react for 18 hours. After the reaction is completed, centrifuge to remove the supernatant and vacuum dry to prepare spherical silicon powder.
[0057] Comparative Example 1 A method for preparing spherical silicon powder for LED display device packaging material comprises the following steps:
[0058] S1, take 4.2g fatty alcohol polyoxyethylene ether and 10g anhydrous ethanol and dissolve them in 100g deionized water, stir and mix at 450r / min at room temperature, add 85g 0.4mol / L sodium silicate solution and continue stirring at a constant speed, then add 16g ethyl acetate, filter the product, wash and dry it to prepare powder A;
[0059] S2, placing powder A in a muffle furnace, and calcining at 600° C. for 2 h in an air atmosphere to obtain a primary product;
[0060] S3, take 10g of the initial product, add 100mL of deionized water, stir and mix at room temperature and ultrasonically disperse, add 12.3g of sodium chloroacetate, add a 0.1mol / L sodium hydroxide solution dropwise to adjust the pH to 11, heat in an oil bath at 100°C for 3h, cool to room temperature and repeatedly wash with deionized water until the pH is neutral, then centrifuge and dry to prepare a carboxylated initial product;
[0061] S4, take 1g of the initial carboxylation product, add 60mL of dichlorothionyl, add 2mL of N,N-dimethylformamide after ultrasonic oscillation, place in an 80°C oil bath, stir and react for 18h, filter, wash and dry to obtain the initial acyl chloride product;
[0062] S5. Take 1 g of the initial product of acyl chloride and add 15 mL of tetrahydrofuran solvent. After ultrasonic dispersion, add 0.5 g of 3,5-di-tert-butyl-4-hydroxybenzylamine and 0.02 g of triethylamine. Stir and mix evenly. Place in a 15°C water bath and stir to react for 12 hours. After the reaction is completed, centrifuge to remove the supernatant and vacuum dry to prepare spherical silicon powder.
[0063] Comparative Example 2 A method for preparing spherical silicon powder for LED display device packaging material comprises the following steps:
[0064] S1, take 6.3g fatty alcohol polyoxyethylene ether and 12g anhydrous ethanol and dissolve them in 120g deionized water, stir and mix at 550r / min at room temperature, add 100g 0.5mol / L sodium silicate solution and continue stirring at a constant speed, then add 18g ethyl acetate, filter and wash the product to prepare a filter cake;
[0065] S2. Add 0.5 g PEG1500 and 50 g deionized water to 10 g of the filter cake, stir and mix at 45° C., and then dry to prepare powder A;
[0066] S3, placing powder A in a tube furnace, and calcining at 300° C. for 2 h in a nitrogen atmosphere to obtain powder B;
[0067] S4, placing powder B in a muffle furnace, and calcining at 320° C. for 2 h in an air atmosphere to obtain powder C;
[0068] S5. Place powder C in a muffle furnace and continue to calcine at 650° C. for 3 h in an air atmosphere to prepare spherical silicon micropowder.
[0069] Performance Testing
[0070] A. The primary products prepared in Examples 1-3 and Comparative Example 1 were subjected to the following tests:
[0071] (1) Yield test: The yield is expressed as the percentage of the mass of the initial product obtained after calcination to the theoretical mass of silicon dioxide in sodium silicate. The calculation formula is: Y% = M / (mW SiO2 ), where M represents the mass of the product obtained after calcination, m represents the mass of sodium silicate, and W SiO2 represents the mass fraction of silicon dioxide in sodium silicate, and the data results are shown in Table 1.
[0072] (2) Suspension rate test: Lambert-Beer law (A=Kbc), at low concentrations, the absorbance A is proportional to the concentration C of the absorbing substance. The change in absorbance over time can be tested to indirectly reflect the change in the concentration of the substance being measured over time, thereby indirectly indicating the suspension rate of the initial product after dispersion in the aqueous solution. Take a certain amount of initial product powder and put it into the aqueous solution, then ultrasonicate it for 30 minutes, shake it evenly, let it stand for 5 minutes, and then start measuring the absorbance of the initial product dispersion. The suspension rate of the initial product dispersion is reflected by calculating the average value of the absorbance change every 10 minutes and the initial absorbance change. The calculation formula is: N%=A 1 / A 2 , where A 1 For the first absorbance test, A 2 The absorbance was measured every 10 minutes, and the data results are shown in Table 1.
[0073] Table 1 Sample performance test results
[0074]
[0075] It can be seen from the data results in Table 1 that the initial products prepared in Examples 1-3 of the present invention have lower average particle sizes than those in Comparative Example 1, and have higher suspension rates after dispersion in aqueous solution. In Comparative Example 1, PEG1500 was not added and only calcination was performed in an air atmosphere, indicating that the addition of PEG1500 can control the agglomeration of particles during the high-temperature calcination process.
[0076] B. The spherical silicon powder prepared in Example 1-3 and Comparative Example 1-2 was subjected to the following tests:
[0077] (1) Oil absorption value test: Weigh 2g of spherical silica powder and place it in a glass cup, add dibutyl phthalate dropwise while stirring until the powder forms a mass, which is the titration end point. Record the mass of dibutyl phthalate (DBP) added, measure three times, and take the average value. The calculation method of oil absorption value is: oil absorption value = m(DBP) / m(spherical silica powder)×100. The data results are shown in Table 2.
[0078] (2) Activation index test: Take 50 mL of deionized water in a beaker, add 2 g of spherical silica powder and stir for 5 min. After stirring, let it stand for 30 min until the solution is clear. Scrape off the sample on the surface of the aqueous solution and filter, dry and weigh the sample that sinks to the bottom of the beaker. The calculation formula of the activation index H is as follows: H = (M 1 / M 2 )×100, where M 1 is the mass of the floating sample-g, M 2 is the mass of the sample that sank to the bottom - g, and the data results are shown in Table 2.
[0079] (3) Wetting contact angle test: The wetting contact angle of the surface of spherical silica powder was measured using a wetting contact angle measuring instrument, and the data results are shown in Table 2.
[0080] Table 2 Sample performance test results
[0081]
[0082] It can be seen from the data results in Table 2 that the spherical silicon micropowder prepared in Examples 1-3 of the present invention has a high activation index, a hydrophobic surface, and a measured oil absorption value lower than that of Comparative Example 1-2, indicating that the adsorption force between the spherical silicon micropowder particles prepared in Examples 1-3 is reduced, the surface energy is reduced, and the degree of agglomeration is reduced.
[0083] C. Preparation of epoxy molding compound: E-44 epoxy resin, methyl hexahydrophthalic anhydride, 2,4,6-tris(dimethylaminomethyl)phenol and propylene oxide benzyl ether were fully mixed, and the spherical silicon powder prepared in Example 1-3 and Comparative Example 1-2 were added respectively, mixed evenly and vacuum degassed, the degassed slurry was poured into a mold and placed in a blast drying oven, cured at 100° C. for 2 h, and the epoxy molding compound cured sample was obtained after demolding. The epoxy molding compound cured sample was subjected to the following tests:
[0084] (1) Bending strength test: Referring to GB / T40564-2021 standard, a cured sample with a size of 80 mm × 15 mm × 4 mm was used for the bending strength test. The test was completed using a universal mechanical testing machine with a pressure head running speed of 2 mm / min. The data results are shown in Table 3.
[0085] (2) Impact strength test: Referring to GB / T1043-93 standard, the impact strength test was carried out using a cured sample with a size of 80 mm × 10 mm × 4 mm. The data results are shown in Table 3.
[0086] (3) Antioxidant performance test: The cured samples were placed in a HJ881 air thermal aging test chamber for high-temperature thermal oxidation aging at 100°C. The aging cycle was divided into four test cycles of 3, 6, 12, and 24 days. Five samples were taken in each cycle, and each sample was tested for oxidation induction time. The data results are shown in Table 3.
[0087] Table 3 Sample performance test results
[0088]
[0089] It can be seen from the data in Table 3 that the oxidation induction time of the epoxy molding materials prepared in Examples 1-3 of the present invention and Comparative Example 1 is relatively long, and after 24 days of thermal oxidative aging, the oxidation induction time is still relatively long, so it has good antioxidant performance. Among them, the oxidation induction time of the epoxy molding materials prepared in Comparative Example 2 is relatively short, and after 24 days of thermal oxidative aging, the oxidation induction time is only 31.5 minutes, which may be due to the fact that the spherical silicon powder component prepared therefrom is not modified with an antioxidant, so the antioxidant performance is relatively poor; in addition, the oxidation induction time of the epoxy molding materials prepared in Examples 1-3 and Comparative Example 1 is relatively short, and the oxidation induction time of the epoxy molding materials prepared in Comparative Example 2 is only 31.5 minutes, which may be due to the fact that the antioxidant is not modified in the spherical silicon powder component prepared therefrom, so the antioxidant performance is relatively poor; in addition, the oxidation induction time of the epoxy molding materials prepared in Examples 1- The prepared epoxy molding compound has excellent flexural strength and impact resistance. In Comparative Example 1, PEG1500 was not added and only calcination was performed in air atmosphere. The measured flexural strength and impact strength were lower than those of Examples 1-3. This may be due to the hard agglomeration of spherical silicon powder during the high-temperature calcination process, resulting in reduced performance. In Comparative Example 2, no antioxidant was modified. The measured flexural strength and impact strength were lower than those of Examples 1-3. This may be due to the poor compatibility between the antioxidant and the epoxy resin, which made it difficult to disperse uniformly in the organic matrix, resulting in reduced performance.
[0090] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0091] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A method for preparing spherical silicon powder for LED display device packaging material, characterized in that: The following steps are involved: S1, dissolving fatty alcohol polyoxyethylene ether and anhydrous ethanol in deionized water, stirring and mixing at room temperature, adding sodium silicate solution and continuing to stir at a constant speed, then adding ethyl acetate, filtering and washing the product to prepare a filter cake; S2, adding PEG1500 and deionized water to the filter cake, stirring and mixing at 45-60° C. and drying to prepare powder A; S3, placing powder A in a tube furnace and calcining in a nitrogen atmosphere to prepare powder B; S4, placing powder B in a muffle furnace and calcining in an air atmosphere to obtain powder C; S5, placing powder C in a muffle furnace, and continuing to calcine in an air atmosphere to obtain a primary product; S6, taking the initial product and adding deionized water, stirring and mixing at room temperature and ultrasonically dispersing, adding sodium chloroacetate, dropping sodium hydroxide solution to adjust the pH to 11-13, heating in an oil bath at 100-120° C. for 3-5 hours, cooling to room temperature and repeatedly washing with deionized water until the pH is neutral, then centrifuging and drying to prepare a carboxylated initial product; S7, taking the initial carboxylation product, adding thionyl chloride, adding N,N-dimethylformamide after ultrasonic oscillation, placing in an oil bath at 80-95° C., stirring and reacting for 18-26 hours, filtering, washing, and drying to obtain an initial acyl chloride product; S8, taking the initial product of acyl chloride, adding tetrahydrofuran solvent, adding 3,5-di-tert-butyl-4-hydroxybenzylamine and triethylamine after ultrasonic dispersion, stirring and mixing evenly, placing in a 15-40° C. water bath, stirring and reacting for 6-18 hours, centrifuging and removing the supernatant after the reaction, and vacuum drying to prepare spherical silicon powder; In step S3, the calcination temperature is 280-350° C., and the calcination time is 1-2 hours; in step S4, the calcination temperature is 300-350° C., and the calcination time is 1-2 hours; in step S5, the calcination temperature is 600-700° C., and the calcination time is 2-3 hours.
2. The method for preparing spherical silicon powder for LED display device packaging material according to claim 1, characterized in that: In step S1, the concentration of the sodium silicate solution is 0.4-0.6 mol / L, the stirring speed is 450-600 r / min, and the stirring time is 4-7 h.
3. The method for preparing spherical silicon powder for LED display device packaging material according to claim 1, characterized in that: In the step S1, the mass ratio of fatty alcohol polyoxyethylene ether, anhydrous ethanol, deionized water, sodium silicate solution and ethyl acetate is 4-8:10-15:90-150:80-120:14-20.
4. The method for preparing spherical silicon powder for LED display device packaging material according to claim 1, characterized in that: In the step S2, the mass ratio of the filter cake, PEG1500 and deionized water is 10:0.25-0.75:
50.
5. The method for preparing spherical silicon powder for LED display device packaging material according to claim 1, characterized in that: The mass ratio of the initial product to sodium chloroacetate in step S6 is 1:1.2-2.
6. The method for preparing spherical silicon powder for LED display device packaging material according to claim 1, characterized in that: In the step S7, the addition ratio of the carboxylation initial product and thionyl chloride is 1 g: 60-100 mL.
7. The method for preparing spherical silicon powder for LED display device packaging material according to claim 1, characterized in that: In the step S8, the mass ratio of the initial product of acyl chloride, 3,5-di-tert-butyl-4-hydroxybenzylamine and triethylamine is 1:0.5-2:0.02-0.1.
Citation Information
Patent Citations
Preparation method of high-density spherical silica powder for electronic packaging
CN114074943A
Production method of active silica powder
CN115974089A
